Histone Methyltransferase DOT1L as a Promising Epigenetic Target for Treatment of Solid Tumors - Alexandrova, Elena; Salvati, Annamaria; Pecoraro, Giovanni; Lamberti, Jessica; Melone, Viola; Sellitto, Assunta; Rizzo, Francesca; Giurato, Giorgio; Tarallo, Roberta; Nassa, Giovanni; Weisz, Alessandro (Frontiers in Genetics, 2022)
The histone lysine methyltransferase DOT1L (DOT1 Like Histone Lysine Methyltransferase) is responsible for epigenetic regulation of gene expression through specific methylation of lysine79 residue of histone H3 (H3K79) in actively transcribed genes. Its normal activity is crucial for embryonic development and adult tissues functions, whereas its aberrant functioning is known to contribute to leukemogenesis. DOT1L is the only lysine methyltransferase that does not contain a SET domain, a feature that allowed development of selective DOT1L inhibitors that are currently investigated in Phase I clinical trials for cancer treatment. Recently, abnormal expression of this enzyme has been associated with poor survival and increased aggressiveness of several solid tumors. In this review are summarized evidences of aberrant DOT1L expression and activity in breast, ovarian, prostate, colon and other solid tumors, and its relationships with biological and clinical behavior of the disease and response to therapies. Current knowledge of the structural basis of DOT1L ability to regulate cell proliferation, invasion, plasticity and stemness, cell cycle progression, cell-to-cell signaling, epithelial-to-mesenchymal transition and chemoresistance, through cooperation with several molecular partners including non-coding RNAs, is also reviewed. Finally, available options for treatment of therapeutically challenging solid tumors by targeting DOT1L are discussed.